Citra Ayu Kumala Sari EFIKASI DIRI, DUKUNGAN SOSIAL DAN RESILIENSI - Kumala Sari, Citra Ayu (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT Every stage of human development in its life span have typical development tasks, which in each step will be faced with a crisis-prone. Ability to continue to live in the face of crisis, difficulty or after experiencing severe stress is called resilience. Resilience is influenced by a variety of things such as personality, ability, self-efficacy and self-esteem, family support and support for this research environment want to find a relationship between self-efficacy and social support with resilience. This research was conducted on 97 students AKBID Ngudia Husada Bangkalan. Data collection tools such as self-efficacy scale as much as 34 aitem, scale social support as many as 36 aitem, and as many as 47 aitem resilience scale. From the analysis of the research data obtained correlation between self-efficacy, social support and resilience produce the R value of 0.669, F = 94.887, with a p-value = 0.000 <0.01, then it can be concluded that there is a significant relationship between self-efficacy, social support and resilience. Key words: Resilience, Self efficacy, Social support